UNASUR and the ability to act face of international conflicts - Kersffeld, Daniel (2013)
The article refers to UNASUR and the management of political crises with important implications and repercussions for South America since 2008. In this logic, the author focuses on the organization ?s role with regard to conflict resolution using case analysis method: Ecuador in 2010 and Paraguay in 2012, both extreme cases of institutional vulnerability.  Therefore, he proposes that UNASUR ?s political and institutional agenda demonstrate a weak point: conflict resolution, directly related with democracy and peace-keeping, important factors for the Nation State.